Immigration as a Context for Learning: What Do We Know About Immigrant Students In Adult Education? - Mary C. Alfred (Adult Education Research Conference, 2004)
The concept of diversity in education has received much attention in the social science literature, and since the mid-eighties, it has been receiving some attention in the literature of adult education. Diversity in adult education has focused primarily on race, class, gender, and sexual orientation and how these contexts impact teaching and learning. Little attention has been paid to culture and migration and how they influence learning among foreign-born students. This presentation will highlight the need for adult educators to give attention to the concept of immigration as a context for learning in adulthood.